(untitled) (KULT_online, 2010)
In her dissertation Lad Trouble: Masculinity and Identity in the British Male Confessional Novel of the 1990s Andrea Ochsner does a close reading of eight male confessional novels (aka: "ladlit") and analyses them as a phenomenon of the alleged crisis of masculinity in Great Britain. According to Ochsner, who is a lecturer for English Literature and Cultural Studies at the University of Basel, this crisis is marked by men’s uncertainty in the face of the emergence of a plurality of masculinity scripts which followed the feminist movement and the focalisation of masculinity as the marked gender in the media of the 1990s. Ochsner argues that ladlit foregrounds the problematic construction of masculine identity at the time. In spite of some minor shortcomings in regards to the author’s theory and method, Lad Trouble is an intelligent study which can be recommended for students and PhD candidates who are looking for examples of how to work productively with sources from contemporary popular culture.